Fall of light - Erikson, Steven (Erikson, Steven. Kharkanas trilogy, 2016)
Steven Erikson returns to the Malazan world with the second book in a dark and revelatory new epic fantasy trilogy. Fall of Light continues to tell the tragic story of the downfall of an ancient realm, a story begun in the critically acclaimed Forge of Darkness. It is a bitter winter and civil war is ravaging Kurald Galain. Urusander's Legion prepares to march on the city of Kharkanas. The rebels' only opposition lies scattered and weakened--bereft of a leader since Anomander's departure in search of his estranged brother. The remaining brother, Silchas Ruin, rules in his stead. He seeks to gather the Houseblades of the Highborn families to him and resurrect the Hust Legion in the southlands, but he is fast running out of time.